Sustainable Operations Management: Evaluating Green Supply Chain Practices and Their Effect on Competitive Advantage - Idun Suwarna; Inganatul Khasanah; Waloyo; Achmad Choerudin (Journal Management & Economics Review (JUMPER), 2026)
This study investigates the role of green supply chain management (GSCM) in enhancing competitive advantage within the framework of sustainable operations management. Drawing on the natural resource–based view and dynamic capability perspectives, the research examines both the direct effect of GSCM practices on competitive advantage and the indirect effects mediated by green innovation and operational efficiency, as well as the moderating role of digital readiness. A quantitative, explanatory research design was employed using cross-sectional survey data collected from 256 managers in manufacturing and logistics-intensive service firms. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to test the proposed hypotheses. The results reveal that GSCM practices significantly and positively influence competitive advantage. Furthermore, green innovation and operational efficiency partially mediate this relationship, indicating that sustainability-driven innovation and efficiency gains are key mechanisms through which green practices create value. In addition, digital readiness strengthens the impact of GSCM on competitive advantage, highlighting the complementary role of digital capabilities in sustainable supply chain implementation. These findings contribute to the sustainable operations management literature by offering an integrated model that explains how environmental practices translate into strategic performance outcomes. Practically, the study provides managers with evidence-based guidance for aligning green supply chain initiatives with innovation, efficiency, and digital transformation to achieve long-term competitive advantage.